Gender differences in written mathematical communication skills of junior high school students - Muhamad Syahidul Qirom; Jarnawi Afgani Dahlan; Turmudi Turmudi (Universitas Hamzanwadi, 2023)
Some research about identifying the differences between male and female students’ written communication skills has been done before. However, the previous research only focused on qualitative studies. Therefore, there is still a lack of empirical proof of the result. This study aims to test whether a significant difference exists between male and female students' written mathematical communication skills and identify their performance difficulties. The subjects were 14 male and 14 female students at the junior high school. The instrument was a test of mathematical communication skills on quadrilateral topics. The research method used was a mixed method with a sequential explanatory design. The data were analyzed using Mann-Whitney U to measure the difference between male and female students’ written mathematical communication skills, and document analysis was conducted to analyze their difficulties in performing written mathematical communication. The results showed that even though there is no significant difference between written mathematical communication skills between male and female students, there is a significant difference when viewed from each indicator. In addition, the difficulties experienced by male and female students are difficulties expressing mathematical ideas using mathematical symbols, using facts and concepts to solve problems, and operating algebraic forms.